Solar origins of space weather and space climate - Komm, Rudolf; Pevtsov, Alexei; Leibacher, John; Gonzalez Hernandez, Irene (Springer New York, 2014)
This topical issue is based on the presentations given at the 26th National Solar Observatory (NSO) Summer Workshop held at the National Solar Observatory/Sacramento Peak, New Mexico, USA from 30 April to 4 May 2012. This unique forum brought together experts in different areas of solar and space physics to help in developing a full picture of the origin of solar phenomena that affect Earth's technological systems.  The articles include theory, model, and observation research on the origin of the solar activity and its cycle, as well as a discussion on how to incorporate the research into space-weather forecasting tools.  This volume is aimed at graduate students and researchers active in solar physics and space science.  Previously published in Solar Physics, Vol. 289/2, 2014.